Insights into the production of toxins and the assembly of spores in Clostridioides difficile - Ramalhete, Sara (2021)
"Clostridioides difficile, a strict anaerobe, sporeforming bacterium, is a major nosocomial pathogen, causing a range of intestinal conditions linked to antibiotic therapy. Because of the number of infections and deaths it causes yearly, the high recurrence rates, the spreading at the community level and the risk of zoonotic transmission, it is classified as an urgent threat by the Centres for Disease Control and Prevention (CDC). Toxins and spores, two of the most important virulence factors in C. difficile, are key elements to determine the severity of the disease and the spreading of the infection, respectively.(...)"